Satisfaction with courses, as one of the axes of academic satisfaction Field study on Tishreen University students (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The research aims to determine the levels of Tishreen University students' on the "satisfaction with courses" scale, and to find out if there are differences between Tishreen University students in the "satisfaction with courses" scale, according to the variables: (gender, academic specialization). A total of (749) undergraduate from Tishreen University students in all faculties, participated in this research, using the "satisfaction with courses" scale. Search results are summarized as follows: The average scores obtained by all faculties for their students' satisfaction with the courses were within the level of satisfaction (average), and there were a differences among the members of the research sample in the scale according to the "gender" variable in favor of females, and there were a differences according to the "academic specialization" variable in favor of the theoretical academic specialization.